Digital Citizenship Literacy among University Students: The Mediating Role of Critical Thinking and Media Awareness in Combating Misinformation - Bambang Yuniarto; Rivo Panji Yudha (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The proliferation of misinformation in digital environments poses a critical challenge for university students, necessitating integrative competency frameworks beyond isolated cognitive skills. This study examined the mediating role of digital citizenship literacy in the relationship between critical thinking, media awareness, and resistance to misinformation among undergraduate students at UIN Siber Syekh Nurjati Cirebon, Indonesia. Employing a quantitative cross-sectional survey design with purposive sampling, data were collected from 300 students across the Tadris IPS and Arabic Language Education programs using a validated five-point Likert-scale instrument. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Results demonstrated that critical thinking and media awareness significantly predicted both digital citizenship literacy and resistance to misinformation. Digital citizenship literacy emerged as the strongest direct predictor of misinformation resistance (β = 0.389, p < 0.001) and significantly partially mediated the effects of critical thinking (β = 0.133) and media awareness (β = 0.116) on misinformation resistance. The full model explained 54.1% of variance in misinformation resistance. These findings suggest that cultivating digital citizenship norms constitutes the most proximal mechanism through which cognitive and media competencies translate into behavioral resistance to false information. Implications for curriculum development, pedagogical practice, and higher education policy are discussed.